Developing a programme theory of a complex, home-based rehabilitation intervention for recovery after an episode of delirium - Shruti Raghuraman; Sarah Morgan-Trimmer; Rob Anderson; Victoria A. Goodwin; Linda Clare; Ellen Richards; Alison Bingham; Elizabeth Goodwin; Rowan Harwood; Annie Hawton; Aseel Mahmoud; Sarah Joanna Richardson; et al. (PLoS ONE, 2026)
Background Delirium in older adults is associated with persistent cognitive and functional decline, increased institutionalisation, and higher mortality. Evidence-based strategies to support recovery after hospitalisation remain limited. This paper outlines the development and refinement of the programme theory underpinning RecoverED, a novel, home-based, multicomponent rehabilitation intervention designed to support post-delirium recovery. Methods We applied a realist-informed, multi-stage process to develop the RecoverED programme theory. This included a rapid realist review, qualitative interviews with older adults, carers, and healthcare professionals, an expert panel workshop, iterative programme theory meetings, and a process evaluation embedded within a single-arm feasibility trial. Data were synthesised into a logic model linking intervention components to hypothesised mechanisms and outcomes. Results The programme theory outlines how cognitive and physical rehabilitation, psychosocial support, health monitoring, lifestyle guidance, and delirium education are expected to promote recovery. Cognitive activities aim to rebuild executive function and daily independence; physical rehabilitation maintains mobility; psychosocial support reduces anxiety and promotes confidence; health monitoring and lifestyle guidance address comorbidities; and delirium education supports sense-making. Key mechanisms include personalised goal-setting, continuity of professional support, and integration with community services. The process evaluation within the feasibility trial confirmed the relevance and acceptability of these pathways, while suggesting refinements to training, psychosocial strategies, and education delivery. Conclusion This paper provides an empirically grounded framework detailing the development and refinement of a programme theory for post-delirium rehabilitation, illustrating the value of flexible, theory-driven approaches to guiding recovery.